Pola Matematika pada Surat Al Ikhlas - Gema Hista Medika (Tamaddun, 2019)
Various studies have been conducted to reveal the order / beauty of the composition and style of language and the contents of Alquran, both in terms of language and numbers contained in Alquran. This study aims to find the mathematical design contained in the letter Al Ikhlas. Surah Al Ikhlas was chosen because of a hadith narrated by Imam Bukhari from Abu Sa'id. Someone heard someone else reading Al Ikhlas and he repeated it. When morning came, he told Prophet Muhammad S.A.W. As if the man was not satisfied with one reading. So the Prophet said, "For the sake of my soul which is in His grasp. The letter is equal to one third of Alquran ". This type of research is a descriptive study that reveals mathematical design in the letter Al Ikhlas. The data used are the constituent figures in Surah Al Ikhlas. The results of the study revealed 12 patterns contained in the letter Al Ikhlas, one of which many different syafatani letters are Fibonacci sequence.